BASLAWÍSh MEKTEP JASÍNDAǴÍ BALALARDA LOGIKALÍQ OQÍW ISKERLIGIN QÁLIPLESTIRIW - Saytbekova, Svetlana Saylaubaevna (ILIM hám JÁMIYET, 2026)
This article examines the mastery of universal learning activities by primary school students to develop their capacity for self-development and self-improvement through the conscious and active acquisition of social experience. Logical learning activities form the foundation of learning and the successful acquisition of new knowledge, skills, and abilities. Logical universal learning activities have a significant impact on the development of primary school students’ learning and cognitive performance and overall cognitive development.